정밀 해저지형 및 해저면 자료를 활용한 동해 남부 연안(울산 일산해변)생태계 서식지 환경 맵핑 연구 - 최순영(SoonYoung Choi); 김창환(ChangHwan Kim); 김원혁(WonHyuck Kim); 노현수(HyunSoo Rho); 박찬홍(ChanHong Park) (자원환경지질, 2021)
We analyzed the characteristics of the habitat environment for the Seonam study area in Ulsan, the southern shore of the East Sea using bathymetry and seafloor environment data. The depth of the study area ranges from about 0 m to 23 m. In the west of the study area, the water depth is shallow with a gentle slope, and the water depth becomes deeper with a steep slope in the east. Due to the right-lateral strike-slip faults located in the continental margin of the East Sea, the fracture surfaces of the seabed rocks are mainly in the N-S direction, which is similar to the direction of the strike faults. Three seafloor types (conglomeratic-grained sandy, coasre-graiend sandy, fine-grained sandy) and rocky bottom area have been classified according to the analyses of the bathymerty, seafloor image, and surface sediment data. The rocky bottom areas are mainly distributed around Seaoam and in the northern and southern coastal area. But the intermediate zone between Seonam and coastal area has no rocky bottom. This intermediate area is expected to have active sedimentation as seawater way. The sandy sediments are widely distributed throughout the study area. Underwater images and UAV images show that Cnidarians, Brachiopods, Mollusks are mostly dominant in the shallow habitat and various Nacellidae, Mytilidae live on the intertidal zone around Seonam. Annelida and Arthropod are dominant in the sandy sediments. The distribution of marine organism in the study area might be greatly influenced by the seafloor type, the composition and particle size distribution of the seafloor sediments. The analysis of habitat environment mapping with bathymetry, seafloor data and underwater images is supposed to contribute to the study of the structure and function of marine ecosystem. 본 연구는 동해 남부 연안의 울산 일산해변에 위치한 선암 주변 해역에 대해 해저지형 및 해저면 환경 자료를 활용하여 서식지 환경 주제도 맵핑 방법으로 서식지 환경 특성을 분석하였다. 연구지역의 전체적인 수심은 노출암인 선암부터 수심 약 0 m ~ 23 m 범위 내에 분포한다. 선암을 중심으로 서쪽으로는 수심이 얕아지면서 경사가 완만해지고 동쪽으로 가면서 수심이 깊어지며 경사가 급해진다. 동해 대륙주변부에 나타난 우수향 주향이동 단층의 영향으로 선암 주변에 나타나는 해저 암반들의 절개 형태는 주향이동 단층방향과 유사한 주로 N-S 방향을 이루고 있다. 해저지형 자료를 기반으로 해저면 영상과 표층퇴적물 자료를 중첩하고 분석하여 연구지역을 수중암반 지대와 총 3가지 type의 퇴적 지대(역질 사질 퇴적물, 조립한 사질 퇴적층, 세립한 사질 퇴적층)로 분류하였다. 수중암반 지대는 선암 주변과 북쪽 및 남쪽 연안 지대에 주로 분포하지만 선암과 연안 사이의 중간 해역은 암반이 거의 존재하지 않는다. 이 중간 해역은 연안과 외해로 연결되는 해수 이동 통로로서 활발한 퇴적활동이 일어났을 것으로 예상된다. 사질 퇴적물은 연구지역 전체에 넓게 분포하고 있다. 수중영상 및 드론사진 자료로 파악한 선암 최근접 해역 서식지는 주로 자포동물, 완족동물 및 연체동물 등이 우점하여 나타났으며 해수면과 맞닿는 노출암 가장자리 지역에는 다양한 배말 및 담치류 생물이 서식하는 것으로 보여진다. 선암 주변 사질 퇴적물 지대에는 주로 환형동물 및 절지동물이 우점하였으며 연구지역의 해양생물 분포 양상은 해저면 Type, 퇴적물의 조성 및 입도 분포 영향을 많이 받는 것으로 파악된다. 이러한 해저지형, 해저면, 수중영상 중첩을 통한 서식지 환경 맵핑 분석은 해양생태계 구조 및 기능 연계 연구에 많은 기여를 할 것으로 판단된다.